Exchange rate movements and firm value: Evidence from European firms across the financial crisis period. Issue 4 (14th September 2015) - Mozumder, Nurul; De Vita, Glauco; Larkin, Charles; Kyaw, Khine S.
Abstract : Purpose: – The purpose of this paper is to investigate the sensitivity of firm value to exchange rate (ER) movements, and the determinants of such exposure for 100 European blue chip companies over 2001-2012. Design/methodology/approach: – The authors adopt a disaggregated framework that distinguishes between Eurozone and non-Eurozone firms, and between financial and non-financial firms across the pre-crisis, crisis and post-crisis periods of the recent financial crisis. Findings: – The authors find no significant difference between Eurozone and non-Eurozone, and financial and non-financial firms. Exposure is found to be higher during the financial crisis, across all sub-samples of firms. In the majority of cases the exposure coefficient is significantly positive, indicating that European firms' stock returns are positively (negatively) affected by depreciation (appreciation) of ERs (indirect quotation). Practical implications: – It is recommended that firms' financial plans budget for higher liquidity levels in order to build up, during "good times", a natural hedge for the higher exposure likely to be faced during periods characterized by greater financial distress. Originality/value: – The main novelty lies in the adoption of a disaggregated framework that discriminates between pre-crisis, crisis and post-crisis periods in order to ascertain the extent to which the recent financial crisis affected the relationship in question.